2003
DOI: 10.1159/000074038
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility in Patterns of IGF Generation with Special Reference to Idiopathic Short Stature

Abstract: Background/Aim: Insulin-like growth factor I (IGF-I) and insulin-lke growth factor binding protein 3 (IGFBP-3) generation tests are both sensitive and specific measures of growth hormone (GH) sensitivity. Recently, the question of reproducibility of IGF generation tests has been raised. We report our analysis of the correlation of low- and high-dose GH IGF-I and IGFBP-3 generation tests among patients with GH deficiency, GH insensitivity, and idiopathic short stature. Methods: A total of 198 subjects were rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 24 publications
3
29
0
2
Order By: Relevance
“…41,42 In contrast, another study showed that in 16 ISS patients with normal baseline IGF-I levels there was a lower than normal IGF-I response on days 5 and 8 of a 7-day IGF-I gen, pos-sibly indicating a partial GH insensitivity. 25 Another study showed that the IGF-I response 24 hours after a single injection of hGH (2 mg/m 2 ) given to 22 prepubertal ISS children was comparable to that of the control children whose mean height though was -1.2 SD. 43 The criteria for classifying the children as ISS in these studies was only that they were short (height < -2SD) and had a normal GH response to pharmacologic provocation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…41,42 In contrast, another study showed that in 16 ISS patients with normal baseline IGF-I levels there was a lower than normal IGF-I response on days 5 and 8 of a 7-day IGF-I gen, pos-sibly indicating a partial GH insensitivity. 25 Another study showed that the IGF-I response 24 hours after a single injection of hGH (2 mg/m 2 ) given to 22 prepubertal ISS children was comparable to that of the control children whose mean height though was -1.2 SD. 43 The criteria for classifying the children as ISS in these studies was only that they were short (height < -2SD) and had a normal GH response to pharmacologic provocation.…”
Section: Discussionmentioning
confidence: 96%
“…[18][19][20][21][22][23][24] It is an invaluable test for diagnosing GHI with a high reproducibility in adults and children. 25 The IGF-I gen has also been used to investigate the relationship between the IGF-I gen response and the growth responses during hGH therapy in children with GH deficiency diagnosed by pharmacologic provocation testing. Rudman et al 26 first studied the IGF I response after a therapeutic trial of ten days with hGH in GHD patients and found a robust increase of IGF-I after a few days of hGH treatment.…”
mentioning
confidence: 99%
“…There is evidence of significant correlation in IGF-1 and IGFBP-3 responses in individuals undergoing sequential IGF-1 generation tests (12).…”
Section: Igf-1 Generation Testmentioning
confidence: 99%
“…22 However, a positive response to the test can be considered an increment of IGF-1 or IGFBP-3 more than twice the coefficient of variation of the assay used. 23 The test identifies almost all the forms of primary GHI.…”
Section: Laboratory Findings Of Primary Igf-1 Deficiencymentioning
confidence: 99%